2011
DOI: 10.1016/j.jpurol.2011.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Observation of infants with SFU Grades 3–4 hydronephrosis: Worsening drainage with serial diuresis renography indicates surgical intervention and helps prevent loss of renal function

Abstract: Infants with Grades 3 and 4 hydronephrosis and preserved DRF may be safely followed with serial DR. Patients with SFU Grade 4 hydronephosis are more likely to require surgery. Worsening drainage on serial DR is a useful indicator for surgical intervention which limits the number of pyeloplasties while preserving DRF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 7 publications
0
22
1
2
Order By: Relevance
“…Only 44% of kidneys with grade 4 HN and 4% of grade 3 HN underwent early surgery for high-grade obstruction. 13 In contrast, Chertin et al have shown that 50% of children followed conservatively went on to surgery. 14 However, one must recognize that the criteria for surgical intervention are variable and may be affected by the surgeons' and parents' wishes.…”
Section: Discussionmentioning
confidence: 97%
“…Only 44% of kidneys with grade 4 HN and 4% of grade 3 HN underwent early surgery for high-grade obstruction. 13 In contrast, Chertin et al have shown that 50% of children followed conservatively went on to surgery. 14 However, one must recognize that the criteria for surgical intervention are variable and may be affected by the surgeons' and parents' wishes.…”
Section: Discussionmentioning
confidence: 97%
“…In recent years, surgical intervention is accepted as a common management when the deterioration of hydronephrosis in unilateral UPJO occurs and when the split function in diuretic scintigraphy is below 40% [14,24,28]. However, in cases like ours especially with bilateral stasis, although the functions decrease, the DRF symmetry does not change.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective study with a large numbers of patients followed with conservative treatment showed the need for conversion to surgical treatment in 22% of patients during a followup period of 10 years 6 . By adopting similar approach, our study…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the diagnose of urinary tract obstruction in children is made by demonstration of hydronephrosis associated with progressive reduction of renal function assessed by radioisotopes 4,5 . The analysis of sequential images obtained by ultrasound associated with scintigraphic assessment of renal function provides objective tools that helps in the decision make to opt for clinical observation or surgery in those children whose hydronephrosis persists in the post-natal life 6 .…”
Section: Introductionmentioning
confidence: 99%